Preferential Solvation of Acetaminophen in Propylene Glycol + Water Co-Solvent Mixtures - Peña, María Ángeles; Delgado, Daniel Ricardo; Martínez, Fleming (Journal of Applied Solution Chemistry and Modeling, 2014)
The preferential solvation parameters defined as the differences between the local mole fraction of solvents around analgesic drug acetaminophen and those for the bulk co-solvent composition in propylene glycol + water mixtures were derived from their thermodynamic properties by means of the inverse Kirkwood-Buff integrals (IKBI) and the quasi-lattice-quasi-chemical (QLQC) methods. It is found that acetaminophen is sensitive to solvation effects, so according to IKBI method the preferential solvation parameter δ´xPG,A, is negative in water-rich mixtures but positive in medium compositions and in co-solvent-rich mixtures. It is conjecturable that in water-rich mixtures the hydrophobic hydration around the aromatic ring and methyl group present in the drug plays a relevant role in the solvation. The bigger drug solvation by co-solvent in mixtures of similar solvent proportions and in propylene glycol-rich mixtures could be due mainly to polarity effects. Otherwise, according to QLQC method, this drug is preferentially solvated by the co-solvent in all the mixtures.